2021
DOI: 10.3389/fped.2021.677955
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Two Types of Staged Laparoscopic Orchiopexy for High Intra-Abdominal Testes in Children: A Retrospective Study From a Single Center

Abstract: Background: To evaluate the efficacy and safety of 2nd-stage laparoscopic traction orchiopexy (Shehata technique) compared to Fowler-Stephens (F-S technique) for high intra-abdominal testes (IATs) in children.Patients and Methods: We performed a retrospective review of all children (<14 years old) who underwent laparoscopic treatment of high IAT in the pediatric surgery center of Yijishan Hospital of Wannan Medical College from April 2016 to April 2020. Participants were divided into the Fowler-Stephens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 30 publications
0
14
0
1
Order By: Relevance
“…In addition, Kollin et al ( 20 ) showed an improvement of testicular growth with early orchidopexy (9 months) when compared to orchidopexy at the age of 3 years. Another factor is that the distance required to lower the testicles in older boys becomes too long, which increases the risk and difficulty of surgery ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kollin et al ( 20 ) showed an improvement of testicular growth with early orchidopexy (9 months) when compared to orchidopexy at the age of 3 years. Another factor is that the distance required to lower the testicles in older boys becomes too long, which increases the risk and difficulty of surgery ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…NPT accounts for 20–35% of UDT, and NPT patients often have short spermatic cord, which have been a challenge for surgeons ( 15 17 ). After the exclusion of non-viable testes, NPT can be classified into intra-abdominal and intracanalicular testes according to the location of the testis ( 4 , 15 ). Various surgical strategies are currently available to address this problem.…”
Section: Discussionmentioning
confidence: 99%
“…In the treatment of high UDT, the modified Prentiss maneuver has a good clinical effect relative to the descending testis through the internal ring. However, there is still controversy over when to use primary laparoscopic orchiopexy ( 4 ). It has been reported that when the testis can reach the contralateral internal ring, primary laparoscopic orchiopexy can be used ( 3 , 5 , 6 , 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, testicles more than 4 cm away from the inner ring are not suitable for this technique. Our team first reported a comparative study of the FSLO and Shehata techniques in the treatment of high IAT in 2021 ( 4 ). The results show that the Shehata technique can effectively retain the main blood supply of the testis and vas deferens, with a high testicular survival rate and obvious advantages.…”
Section: Treatment Of Cryptorchidismmentioning
confidence: 99%
“…Cryptorchidism is a common congenital malformation in pediatric urology which is also known as undescended testis (UDT) or incomplete testicular descent (1)(2)(3). According to the location of the testis, cryptorchidism can be divided into palpable testis and non-palpable testis (NPT), and palpable testis accounts for more than 80% of cryptorchidism cases (4). Cryptorchidism is associated with testicular tumors and hernia, and thus, it requires active treatment (5).…”
Section: Introductionmentioning
confidence: 99%